Korespondencja Stanisława Augusta z konsyliarzem Rady Nieustającej Antonim Dziekońskim w latach 1779–1784 - Kobierecki, Michał (Przegląd Nauk Historycznych, 2013)
The article discusses the correspondence between King Stanisław August and Antoni Dziekoński in the years 1779–1784. The monarch’s employee and correspondent embarked on his career in Lithuania, where he held district offices in the Wołkowyski District, followed by military offices; he also served as a Member of Parliament in 1766. As a Lithuanian Field Guard, he became a member of the Permanent Council in 1775 and acted in it until the year of 1786. At that time he became a staff member in Stanisław August’s cabinet, implementing the assignments he had been given. The correspondence between the monarch and A. Dziekoński contains a plethora of compelling subjects, which concern various matters. They involve the question of personal policy within the royalist party in Lithuania regarding district offices or posts. It also refers to A. Dziekoński’s endeavours to be appointed to the Lithuanian Court Chamberlain office. A weighty matter was the preparations of the town of Grodno to hold a seym in 1784. Furthermore, he managed the royal estate in Lithuania, after it had been relinquished by Antoni Tyzenhauz, the then Lithuanian Court Chamberlain. Occasionally he attempted to offer assistance to persons who had come into conflict with the law, not necessarily of their own accord. Undoubtedly he played a significant role in the contacts between king Stanisław August and the supplicants, on the one hand as an intermediary, to whom requests were submitted, on the other hand he executed the monarch’s orders. He was occupied both with serious matters concerning the activity of the royalist party in Lithuania and trivial ones, such as keeping the kennel which had been presented to king Stanisław August. Furthermore, the content of the letters reveals the attitudes and relations between the ruler and his loyal servant fulfilling the royal orders, which enables the researcher to analyse the atmosphere between the two correspondents.